ChemInform Abstract: Microwave‐Assisted, Rhodium(III)‐Catalyzed N‐Annulation Reactions of Aryl and α, β‐Unsaturated Ketones with Alkynes. Issue 23 (10th June 2014) - Lee, Hyejeong; Sim, Yong‐Kyun; Park, Jung‐Woo; Jun, Chul‐Ho
Abstract The title process leads to isoquinolines and pyridines from corresponding aromatic ketones [e.g. (I)] and enones [e.g. (XV)], respectively.